Analisis Kemampuan Literasi Matematika Siswa Kelas VIII Ditinjau Dari Perbedaan Gender Di MTsN 1 Mataram Tahun Ajaran 2020/2021 - Rizkian Agung Jamaesa; Sudi Prayitno; Wahidaturrahmi; Hapipi Hapipi (Griya Journal of Mathematics Education and Application, 2022)
The purpose of this study was to describe the level of mathematical literacy ability of class VIII MTsN 1 Mataram based on gender. The research is quantitative desciptive research which method are used to describe, explain various variabel in the study as expressed the documentary materials. The assessment system in this study uses 2 methods, namely mathematical literacy and analytical problem solving. Mathematical literacy has 6 (six) levels in measurement and consists of three aspects, namely content, context, and cognitive aspects, while for assessment using analytical problem solving there are 3 (three) levels, namely low, medium and high. The data collection technique used a questionnaire in the form of mathematical literacy test questions that had been approved by 3 validators. Based on the results of the research, the level of mathematical literacy skills, based on mathematical literacy female dominant at level 3 which means that students are able to apply the basic algorithm, formulate and carry out the procedure and can select and apply strategies to solve simple and the mathematical literacy skills of male students are dominant at level 2 which means that students are able to apply the basic algorithm, formulate and carry out the procedure. Based on analytical problem solving students' mathematical literacy skills are at low and medium levels where female mathematical literacy skills are higher compared to male. Bassed t-test 2 sampel independent mathematical literacy ability male and female doesn’t have a significant difference.